A highly water-soluble dendro[60]fullerene - Brettreich, Michael; Hirsch, Andreas (Tetrahedron Letters, 1998)
The nucleophilic cyclopropanation of C with a second generation bis(polyamide)-malonate dendrimer and the subsequent deprotection of the terminal t-butyl groups provides a dendro[60]fullerene with 18 carboxylic groups in the periphery. This dendritic monoadduct of C is highly water- soluble.